Pelatihan Produksi Nugget Berbasis Daging Ayam Kampung pada Kelompok Peternak Ayam di Desa Sidelego-Merangin - Azis, Abdul; Afriani, Afriani; Lukman, Haris; Nelwida, Nelwida; Berliana, Berliana; Nurhayati, Nurhayati; Muthalib, R A; Depison, Depison; Alwi, Yun; Insulistyowati, Anie; Handoko, Heru (Universitas PGRI Semarang, 2024)
The recognition of processing chicken nuggets by the group of farmers in Sidelego village is an alternative to increase added value from the use of meat from the old chicken. This community service aims to increase the knowledge and skills of the farmers in Sidelego village utilizing chicken meat as a chicken nugget product. The community service activity involved 20 participants from a farmer's group in Sidelego village. The procedure for this activity is designed in 4 stages, including the preparation, training, demonstration, and evaluation of the activity. The farmers' first evaluation showed that most had consumed chicken nuggets; however, they had never tried to make chicken nugget products. The farmers' response to this activity was perfect, and they actively participated in the delivery of training materials and the practice of making chicken nuggets. The evaluation at the end of the activity, most of the participants (80-90%) were able to understand the materials of the training, and they could make chicken nugget products with a high level of acquisition. About 70% of participants with a moderate acquisition level could design modified nugget products with various kinds or variants, such as nuggets with additional ingredients, such as various types of vegetables or tempeh. Based on the preference test, most of the participants gave an assessment of chicken nugget products in the range of preference levels from the moderate to like a category on the color (80.00%), aroma (80%), taste (70.00%) and texture (80%). It was concluded that most participants (80-90%) understood the process of producing chicken nuggets. The chicken nuggets product can be received very well with the preference level in all categories (color, aroma, taste, and texture).